2020
DOI: 10.1021/acsami.0c02129
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Capture Using Zr-Based Metal–Organic Frameworks (Zr-MOFs): Adsorption Performance and Mechanism

Abstract: The effective capture of radioiodine, produced or released from nuclear-related activities, is of paramount importance for the sustainable development of nuclear energy. Here, a series of zirconium-based metal−organic frameworks (Zr-MOFs), with a Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 cluster and various carboxylate linkers, were investigated for the capture of volatile iodine. Their adsorption kinetics and recyclability were investigated in dry and humid environments. The structural change of Zr-MOFs during iodine trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(196 citation statements)
references
References 52 publications
5
182
0
Order By: Relevance
“…While SION-8 is an insulator, the I 2 -adsorbed SION-8 (SION-8*I 2 ) showed electrical conductivity, proving the donor-acceptor charge transfer. Similarly, NU-1000 has been studied for the capture of volatile I 2 by Chen et al 224 NU-1000 could adsorb 1.45 g I 2 /g MOF at 80 1C, thanks to the presence of the -OH groups of Zr 6 nodes and enriched p-conjugated electron clouds on pyrene. Pyrene can donate abundant negative charges, making NU-1000 convenient to host iodine.…”
mentioning
confidence: 99%
“…While SION-8 is an insulator, the I 2 -adsorbed SION-8 (SION-8*I 2 ) showed electrical conductivity, proving the donor-acceptor charge transfer. Similarly, NU-1000 has been studied for the capture of volatile I 2 by Chen et al 224 NU-1000 could adsorb 1.45 g I 2 /g MOF at 80 1C, thanks to the presence of the -OH groups of Zr 6 nodes and enriched p-conjugated electron clouds on pyrene. Pyrene can donate abundant negative charges, making NU-1000 convenient to host iodine.…”
mentioning
confidence: 99%
“…4(b), the three 808-PVDFx beads have a lower weight gain, exhibiting the similar patterns as their powder counterparts, due to the hydrophilic Zr nodes in the MOFs. 13 Because of the huge difference in molecular weights of iodine and water molecules, the weight ratio of adsorbed water is very small. 34,35 Besides, there may be a cooperative adsorption effect between H 2 O and iodine molecules.…”
Section: Characterization Of Mof-808 Beadsmentioning
confidence: 99%
“…Raman mapping of area integral intensities was detected to explore the species of the adsorbed iodine on the external surfaces of the beads. Two typical bands, which are centered at 110 cm À1 and 170 cm À1 , ascribed to I 3 À species and packed iodine solid, respectively, 13,40 were recorded and integrated. The Raman mapping images of 808-PVDF0.7 with low loading amount (5% wt) of iodine, 808-PVDF0.7-5% I, are shown as Fig.…”
Section: Characterization Of Mof-808 Beadsmentioning
confidence: 99%
See 1 more Smart Citation
“…is is caused by the disorder of the crystal structure and the scattering of the iodine element remaining in the crystal during polymerization. Cheng et al (2020) reported that the intensity of all the peaks for the porous MOF-808 crystal decreases gradually, because of the increased di use scattering of the absorbed iodine. In addition, SEM images of these cubic CD-MOF crystals showed hardly any change.…”
Section: Copolymerization Of Tth and Edot In Cd-mofmentioning
confidence: 99%